2010
DOI: 10.1086/653495
|View full text |Cite
|
Sign up to set email alerts
|

Select Human Anthrax Protective Antigen Epitope‐Specific Antibodies Provide Protection from Lethal Toxin Challenge

Abstract: Bacillus anthracis remains a serious bioterrorism concern, and the currently licensed vaccine remains an incomplete solution for population protection from inhalation anthrax and has been associated with concerns regarding efficacy and safety. Thus, understanding how to generate long lasting protective immunity with reduced immunizations or providing protection through post exposure immunotherapeutics are long sought goals. Through evaluation of a large military cohort, we characterized the levels of antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(89 citation statements)
references
References 48 publications
(64 reference statements)
5
83
1
Order By: Relevance
“…Cysteine substitutions at any of these 4 amino acids resulted in the inhibition of PA activity by at least 100-fold 64 . Additionally, antibodies directed against the epitope P232 to V247, which contain two of these residues, were found in 4 of 6 serum samples from AVA vaccinated human donors with high neutralizing serum titers 78 . Affinity purified antibodies directed against P232 to V247 (designated as PA6 in this study) were tested against LT and shown to provide 50% protection of RAW 264.7 cells.…”
Section: Domain I'mentioning
confidence: 99%
See 4 more Smart Citations
“…Cysteine substitutions at any of these 4 amino acids resulted in the inhibition of PA activity by at least 100-fold 64 . Additionally, antibodies directed against the epitope P232 to V247, which contain two of these residues, were found in 4 of 6 serum samples from AVA vaccinated human donors with high neutralizing serum titers 78 . Affinity purified antibodies directed against P232 to V247 (designated as PA6 in this study) were tested against LT and shown to provide 50% protection of RAW 264.7 cells.…”
Section: Domain I'mentioning
confidence: 99%
“…78 . This shows that antibodies directed against this region contribute to neutralization, but it is unknown whether they are sufficient on their own for providing protection against anthrax toxin.…”
Section: Subunit Vaccinesmentioning
confidence: 99%
See 3 more Smart Citations